Creative thinking: a programme to develop the empowerment of creativity: Analysis and evaluation of results - Molares-Cardoso, Julinda (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
In a globalized and changing world, the development of the creative thinking is essential. This research analyses the performance and creative skills of the students who attend to the Degree in Public Relations and Advertising of Vigo University through the implementation of a programme to empower creativity. The methodology is quantitative and descriptive and the results are shown in four exercises which have been developed from the point of view of gamification. The findings underscore the positive effects of these kinds of dinamics in the development of the creative thinking and the needs to improve certain areas.